A methods engineering study on Marchant Stainless Fabricators, Inc. - Balingit, Mary Dian.; Garcia, Czarhina; Maghuyop, Lourdes; Tan, Katherine (Diliman, Quezon City College of Engineering, 2004)
Identification of the possible sites for improvement in an industry is one of the major advantages of Methods Engineering. Typical subjects for such study are companies dealing with the production of either new or existing products with high production costs and low profit. Firms facing the challenge of maintaining their product's quality, as well as their place in the market are considered candidates for the applications of methods engineering. The study conducted on Marchant Stainless Steel Fabricators revolved around the identification of the company's possible sites for improvement. Acknowledgement of these areas for consideration may pave the way for the improvement of the company's product quality and increase in efficiency of their production processes. The fast growing food service industry entails a large supply of kitchen equipments to satisfy their primary concern of rendering service to their customers. Hence, the study dealt with the fabrication of kitchen equipment that are known to project the greatest demand originating from the food service industry. Products considered in this study, based on the aforementioned criterion, were the four open top burner and the regular bun racks. Data gathered during the documentation of the processing of the products and the time study, were subjected to analysis. Results on these were used to determine the core problems. Such core problems include poor material handling, ineffective job orientation, lack of expertise of workers, indefinite production schedule, low utilization of the bending machine, poor ventilation and lighting, repetitive alternating operations, difficulty in forming metal sheets, undefined flow of operations and excessive noise. The study revealed that these core problems were the reasons leading to process delays. In order to avoid the main effect presented, each problem was analyzed. Cost and ease of implementation were the qualifications considered in rating each alternative. In the generation of alternaties, decision statements were made and each alternative were weighed until all final choice were reached. Following these, proposals for implementation procedures regarding each alternative chosen was then constructed. Furthermore, possible recommendations for further study were also considered.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis